Relations of Moturidi and Samarkandi - ugli, Abduhamidov Muhammadjon Abduhalim (Indonesian Journal Publisher, 2024)
This article highlights the relationship between Moturidi and Samarkandi, with a focus on the work “Kitab as-savod al-azam” and its significant theological elements. The study explores the connection between the two scholars, investigating whether Hakim Samarkandi was a disciple of Moturidi or merely a contemporary. The article also examines the impact of “Kitab as-savod al-azam” on Moturidi theology and its relevance to traditional Hanafi doctrine. The research delves into the theological discourse between the two scholars, addressing conflicting views on various theological issues.